2017
DOI: 10.1007/s11207-017-1091-6
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Successive Coronal Mass Ejections: A Review

Abstract: We present a review of the different aspects associated with the interaction of successive coronal mass ejections (CMEs) in the corona and inner heliosphere, focusing on the initiation of series of CMEs, their interaction in the heliosphere, the particle acceleration associated with successive CMEs, and the effect of compound events on Earth's magnetosphere. The two main mechanisms resulting in the eruption of series of CMEs are sympathetic eruptions, when one eruption triggers another, and homologous eruption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
181
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(191 citation statements)
references
References 265 publications
(397 reference statements)
9
181
0
1
Order By: Relevance
“…As stated by Burlaga et al (2002) merging is a nonlinear and irreversible process, where memory of the source conditions is lost. The merging takes place due to magnetic reconnection between the consecutive CMEs (see Lugaz et al 2017, and references therein). Figure 29 shows an example of a complex ejecta observed during September Fig.…”
Section: Observations Of Icme Interactions In the Heliospherementioning
confidence: 99%
“…As stated by Burlaga et al (2002) merging is a nonlinear and irreversible process, where memory of the source conditions is lost. The merging takes place due to magnetic reconnection between the consecutive CMEs (see Lugaz et al 2017, and references therein). Figure 29 shows an example of a complex ejecta observed during September Fig.…”
Section: Observations Of Icme Interactions In the Heliospherementioning
confidence: 99%
“…ICMEs are always accompanied by solar winds. Interplanetary propagation of CMEs face aerodynamic drag by solar winds and are accelerated or decelerated on the basis of their relative speed with respect to solar wind i.e., the CMEs which are faster than the solar wind are decelerated while the one which has lower speed is accelerated [12], [30] - [33]. The acceleration of CME solely depends on their interaction with solar wind.…”
Section: Coronal Mass Ejections (Cmes)mentioning
confidence: 99%
“…The acceleration of CME solely depends on their interaction with solar wind. Since the acceleration of CME largely depends on the amount of energy present at the trigger point, there can be an interaction between two CMEs (which were erupted at different times) and due to this their configuration changes [33]. CME also accelerates the energetic particles emanating from the Sun towards the interplanetary space.…”
Section: Coronal Mass Ejections (Cmes)mentioning
confidence: 99%
“…Gopalswamy et al, 2009;Xiong, Zheng, and Wang, 2009;Temmer et al, , 2014Shen et al, 2012a;Liu et al, , 2014Martínez-Oliveros et al, 2012;Webb et al, 2013;Shen et al, 2011Shen et al, , 2012bShen et al, , 2013Shen et al, , 2016Mishra and Srivastava, 2014;Mishra, Srivastava, and Chakrabarty, 2015;Mishra, Srivastava, and Singh, 2015;Mishra, Wang, and Srivastava, 2016;Shanmugaraju et al, 2014;Colaninno and Vourlidas, 2015). A comprehensive review about the interaction of successive CMEs and consequences in particle acceleration and geoeffectiveness by Lugaz et al (2017) can be found in the Topical Collection called Earth-affecting Solar Transients.…”
Section: Introductionmentioning
confidence: 99%